MAPPING CORAL REEF AREA OF KABUNG ISLAND USING SATELLITE IMAGERY - Sari, Sherin Sastia; Nurrahman, Yusuf Arief; Helena, Shifa (Dept. Marine Science, 2022)
Kabung Island is located in Bengkayang Regency, West Kalimantan. Kabung Island has a small area but has wealth and beauty that can attract tourists to come for a tour, one of which is the beauty of coral reefs. Monitoring the condition of coral reefs can be done in various ways. The utilization of remote sensing with different satellite images can monitor coral reefs in a wide area. This study aimed to create a map of the location of coral reefs on Kabung Island using medium resolution and high-resolution images. This study uses primary data, which specific methods will then process. The data are Sentinel-2 MSI Level 2A Satellite Imagery for mediumresolution image data and Birds Eye Satellite Imagery for high resolution imagery. The results of the classification of Bird Eye images obtained that the area of each class is the area of live coral on Kabung Island of 1.969 ha, dead coral of 1.1521 ha and sand or substrate of 1.7451 ha. It can be seen that the live coral class dominates in the shallow marine bottom habitat on Kabung Island, while the dead coral has the lowest area. The accuracy of test results obtained in this study was 93.4%.